Industrial–educational collaboration case study for fur design education - Lee, Nahyun; Kim, Nayun; Kim, Gahyun; Ha, Jisoo (Fashion and textiles, 2017)
This paper is a case study on industrial–educational collaboration program between KF and SNU for fur design education. Industrial-educational collaboration program was done by Royal Danish Embassy in South Korea in commemoration of the 55th anniversary of both nations’ diplomatic ties. Major tasks of industrial–educational collaboration are as follows. For 3 years from 2014 to 2016, fur design education workshops and fashion shows were held in Seoul of South Korea and Copenhagen of Denmark under mutual cooperation. The goal of a workshop was development of various and creative fur designs along with popularization of fur industry. It has significance in that it contributed to the development of fur industry through creative fur design education for superior students of the world and provided them with opportunities to expand a scope of design through experiencing materials. Future fur industry and global fashion design are expected to develop with much interest and participation through such a successful industrial–educational collaboration program.